Prevalence and Causes of Visual Impairment in a Chinese Adult Population: The Taizhou Eye Study - Tang, Yating; Wang, Xiaofeng; Wang, Jiucun; Huang, Wei; Gao, Yaping; Luo, Yi; Lu, Yi (Ophthalmology (Rochester, Minn.), 2015)
To study the current prevalence and causes of low vision and blindness in an adult Chinese population. Population-based, cross-sectional study. We used a random cluster sampling method and evaluated 10 234 eligible subjects ≥45 years old (response rate, 78.1%) in the Taizhou Eye Study. Examinations were performed from July 2012 through December 2013. Participants underwent a detailed examination, including uncorrected visual acuity, best-corrected visual acuity (BCVA), intraocular pressure, axial length, slit-lamp, and fundus examinations to evaluate the prevalence and primary causes of visual impairment (VI). We defined low vision and blindness according to the World Health Organization (WHO) criteria (low vision: BCVA, <20/63-≥20/400; blindness: BCVA, <20/400 in the better eye) and United States criteria (low vision: BCVA, <20/40-≥20/200; blindness: BCVA, <20/200 in the better eye). Using the WHO BCVA criteria, the standardized prevalence of bilateral low vision and blindness were 5.1% and 1.0%, respectively. Using the United States BCVA criteria, the standardized prevalence were 12.8% and 1.5%, respectively. Using the WHO criteria, the primary causes of bilateral low vision and blindness were cataract (59.1% and 48.5%, respectively), myopic macular degeneration (17.6% and 17.2%, respectively), and age-related macular degeneration (11.6% and 10.1%, respectively). The primary causes of monocular low vision were cataract (55.6%), age-related macular degeneration (12.6%), and myopic macular degeneration (8.9%), whereas those of monocular blindness were cataract (46.8%), atrophy of eyeball or prosthetic eye (10.2%), and cornea opacity (7.3%). A further analysis revealed that in adults 45-59 years old, myopic macular degeneration (59.6% and 27.2%, respectively) and cataract (13.8% and 23.4%, respectively) were the leading causes of bilateral and monocular VI. In adults ≥60 years old, cataract (66.8% and 61.2%, respectively) and age-related macular degeneration (12.6% and 11.8%, respectively) were the primary causes of bilateral and monocular VI. The prevalence of low vision and blindness in Chinese adults remains a severe public health problem. In the Taizhou Eye Study, cataract was the leading cause of low vision and blindness. Myopic macular degeneration and cataract were the primary causes of VI in adults 45-59 years and ≥60 years old, respectively.